Students' Reflective Thinking Skills in Mathematics Learning: Systematic Literature Review (Journal of Didactic Studies, 2024)
Students' reflective thinking skills are very important in achieving educa- tional goals. Reflective thinking skills have a big role in the process of solving the problems. The involvement of reflective thinking processes in mathematics learning will influence the achievement of learning outcomes. This research aims to describe the results of research on students' reflective thinking skills in mathematics learning. The method used in this research, namely systematic literature review (SLR) which is guided by the Preferred Reporting Items for Systematic Review and MetaAnalysis (PRISMA). This research has collected information and study results from researchers from all over the world to provide a general overview of research on students' reflective thinking in mathematics learning. The key question in this research is how these articles are distributed based on year of publication, level of education, method, conceptual framework of reflective thinking, levels and indicators of reflective thinking. The results of the research show that studies related to reflective thinking skills in 2017 to 2023 are a period of growth in the publication of articles in reputable international journals, especially in scopus, research on reflective thinking is mostly carried out at the secondary school level, most studies on reflective thinking apply qualitative methods, it is obtained several levels and indicators in students' reflective thinking and some do not report them. The implications of this research will be reference material that describes students' reflective thinking to improve mathematics learning outcomes.